Legal Analysis of Laundering in Article 137 Letter a of Law Number 35 of 2009 on Narcotics (Case Study Supreme Court Decision No. 994 PK / Pid.Sus / 2024) - Asliani, Asliani (International Asia Of Law and Money Laundering (IAML), 2025)
Current technological developments help society and a country in doing daily activities, these activities can be engaged in economic, social and political. Wrong one act that uses the development of technology in the form of crimes involving financial system for example divert some money obtained from the proceeds of crime generally referred to as money laundering or money laundering ang done with trying to hide money through the bank to look like money earned from legitimate activity and avoid suspicion that the money is illegal. As for the a problem in this study is how criminal liability perpetrators money laundering from narcotics. Legal research methods used in this study is the type of normative juridical research that reveals rules - normative and Basic Rules - the principle of law which is the policy in formulating action criminal and analyze library materials, one of which is the Supreme Court decision number 994 PK / Pid.Sus/2024. Based on the results of research on the Supreme Court Decision No. 994 PK/Pid.Sus / 2024 can be concluded that that the judge decided the case based on elements - elements of Juridical consideration of judges based on Law- Law No. 35 of 2009 on narcotics and witness statements and tools evidence is a legal legal conclusion on the facts revealed in the trial. For that Panel of judges to be more wise in sentencing the perpetrators of criminal acts Money laundering derived from narcotics acts by imposing penalties that can provide a deterrent effect for the perpetrators of the crime.